Efficacy of Probiotic Saccharomyces boulardii as an Adjuvant Therapy in Acute Childhood Diarrhoea - Dash, Dillip Kumar; Dash, Mrutunjaya; Mohanty, M.D.; Acharya, Naresh (Journal of Nepal Paediatric Society, 2017)
Introduction: Administration of S. boulardii in addition to rehydration therapy in diarrhea found to be beneficial in many aspects owing to a variety of causes and importantly it is was not associated with any adverse effects. Material and Methods: We conducted a prospective study of children suffering from acute diarrhoea, at a private tertiary care hospital. Children were divided into 2 groups randomly as per odd(Group 1 ) and even (Group 2) bed allotted in indoor at the time of admission: Group 1 included children on oral rehydration therapy (ORT) + Zinc + Saccharomyces boulardii (Probiotic 5 billion CFU twice daily) and Group 2 comprised of children on ORT+ Zinc. Our objective was to systematically review data on the effect of S. boulardii on acute childhood diarrhoea. Results: Out of a total of 126 children less than 2 years, 2-6 years and 6-14 years were 72 (57.14%), 42(33.33%) and 12(09.52%) respectively. The duration of diarrhoea in Group 1 was 26.31 hours and Group 2 was 47.81 hours (p<0.01). The frequency of diarrhoea showed improvement within 24 and 72 hours in Group 1 and Group 2 respectively (p<0.01).Similarly, the mean duration of hospital stay was 2.68 days in Group 1 and 4.8 days in Group 2.The treatment cost was INR 850 and INR 1650 while social cost was INR 1250 and 2600 in Group 1 and 2 respectively. Conclusion:This study shows that S. boulardii reduced the duration, frequency and hospital stay of diarrhoea thereby reducing the treatment and social costs. J Nepal Paediatr Soc 2016;36(3):250-255